The Effect of Temperature on the Development of Seagrass in the Waters of Pramuka Island, Kepulauan Seribu Regency, Jakarta, Indonesia - Hizkia Tuejeh; Elva Susanti Meylani; Muzani Jalaludin (Jurnal Pendidikan Geografi Gea, 2023)
This research aims to analyze the correlation between sea surface temperature with seagrass bed in Pramuka Island, Kepulauan Seribu Regency. The observation to obtain the primary data which held on December 7th, 2019, was done through direct surveillance of existing seagrasses, and by doing some interviews with locals. Information from books, journals, reports, and satellite images are used as secondary data. Both data were processed with analytics description method to conclude the result. The finding shows that Pramuka Island has the optimal temperature for seagrass development. While temperature plays a crucial role in seagrass physiology and biomass production, there are other numerous environment and anthropogenic factors that affect seagrass distribution and quality. Furthermore, the local community activities are also affecting the seagrass ecosystem, especially those activities in the economic sector such as tourism and construction. Therefore, education on the importance of maintaining seagrass ecosystems will be needed by both local residents as well travelling tourists.